The role of evaluative nouns in shaping modern English movie discourse: An axiological and morphological analysis - Irena Snikhovska; Larysa Soloviova; Julia Bereziuk; Svitlana Poplavska; Zoia Zalibovska-Ilnitska (Universitas Ahmad Dahlan, 2026)
Evaluative language has been widely examined, but evaluative nouns in cinematic discourse remain insufficiently studied. This study addresses this gap by systematically analyzing evaluative nouns in English movie dialogue. A sample of 176 lexemes with explicit evaluative marking was selected from authoritative dictionaries and analyzed using The Movie Corpus with a frequency threshold of ≥10 occurrences. The study combines lexicographic analysis with corpus-based methods to identify recurrent patterns and contextual usage. The findings reveal a strong quantitative asymmetry between negative and positive evaluative nouns (84 vs. 8), indicating a linguistic tendency to mark deviations in cinematic language. Morphologically, evaluative meanings are primarily realized through suffixation, with -y/-ie, -ling, -er, and -o demonstrating high productivity in the dataset. These suffixes exhibit functional ambivalence, encoding both pejorative and meliorative meanings depending on context. The results show that evaluative nouns function as recurrent elements in cinematic dialogue, contributing to character construction and interactional dynamics. This study contributes to evaluative morphology and discourse analysis by integrating lexicographic and corpus-based approaches. The findings may inform research in film studies, translation, and applied linguistics.